Anxiety, stress and depression levels among nurses of educational hospitals in Iran: Time of performing nursing care for suspected and confirmed COVID-19 patients - Hojjat Sheikhbardsiri; Mohammad Mahdi Doustmohammadi; Parya Jangipour Afshar; Majid Heidarijamebozorgi; Hamidreza Khankeh; Mehdi Beyramijam (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: Following the global emergency of coronavirus disease 2019 (COVID-19), health-care workers, especially nurses were encountered with an increasing workload. Therefore, due to the importance of this issue, the present study aimed to examine stress, anxiety, and depression levels among nurses during the COVID-19 pandemic in Iran. MATERIALS AND METHODS: This cross-sectional study was conducted in four educational hospitals affiliated to Kerman University of Medical Sciences in 2020. The standard Depression, Anxiety and Stress Scale-21 questionnaire was applied to assess the levels of stress, anxiety, and depression in nurse personnel with a census method (n = 403). Data were analyzed using descriptive statistics and analytic statistics such as Kolmogorov-Smirnov, Mann-Whitney, Kruskal-Wallis, and multiple linear regression tests through the version 20, SPSS Inc., Chicago, IL, USA, Software at the level of P < 0.05. RESULTS: The results of the study showed that the mean scores of depressions (9.18 ± 4.45), stress (9.62 ± 4.94), and anxiety (10.32 ± 4.85) in nurses were at moderate level. A significant relationship was observed between stressed, anxious, and depressed participants in the gender, marital status, level of education, and working hours per month. No statistically significant relationship was found between other demographic variables including age, work experience, and employment status with anxiety, depression, and stress categories. CONCLUSION: The results of this study can increase the awareness of health system managers, especially hospitals, about the level of stress, anxiety, and depression and can help in order to provide psychological support programs for improving the mental health of nurses during the COVID-19 pandemic.